Pengaruh Budaya Organisasi, Disiplin Kerja dan Motivasi Kerja Terhadap Produktivitas Pegawai di Badan Pengelolaan Aset Daerah Provinsi DKI Jakarta - Peri Suryanto; Yulianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The productivity level of employees at the Regional Asset Management Agency of DKI Jakarta Province in 2022 and 2023 experienced a decline in time management and work efficiency. This study aims to analyze and evaluate the extent to which Organizational Culture, Work Discipline, and Work Motivation influence Employee Productivity at BPAD DKI Jakarta Province. The research adopts a quantitative approach with a population of 91 individuals. The sampling method employed is saturated sampling, where the entire population is taken as the sample. Research data were collected through questionnaire distribution and analyzed using SPSS 25 software with statistical analysis techniques. The results revealed that Organizational Culture has an influence of 59.9%, Work Discipline has an influence of 58.4%, and Work Motivation has an influence of 53.9%. Collectively, the influence of Organizational Culture, Work Discipline, and Work Motivation is 65.5%. Based on these findings, it is recommended that BPAD DKI Jakarta Province enhance its focus on employee development, attendance consistency, clarity in promotion procedures, and the improvement of quality standards to foster a work culture that supports productivity and organizational progress.